Camelina Oil as Ethiopia’s Next Edible Oil: Insights into Chemical Composition and Agro-Ecological Adaptability—A Review - Kidane, B.; Hunde, W.; Urugo, M.M.; Tessema, Fikadu; Teka, T.A. (2025)
Camelina sativa, commonly known as Camelina, has emerged as a promising oilseed crop due to its remarkable adaptability to various environmental conditions and its rich nutritional profile. The high content of dietary polyunsaturated fatty acids (PUFAs), particularly omega-3 fatty acids, including alpha-linolenic acid (ALA), tocopherols, and phytosterols, distinguishes this oilseed and sets it apart from many traditional vegetable oils. Its advantageous agronomic characteristics, such as strong drought resistance, early maturation, low input requirements, and the ability to be cultivated twice in a single season, position Camelina as a viable cash crop capable of meeting diverse market demands ranging from dietary supplements to cosmetics and high-quality animal feed. In Ethiopia, where the vegetable oil market faces significant challenges, approximately 95% of domestic consumption is met through imports, resulting in substantial foreign exchange expenditures. This reliance highlights the urgent need for local oil sources to enhance nutritional diversity and food security. Camelina’s adaptability to Ethiopia’s diverse agro-ecological zones offers a unique opportunity to cultivate this crop under various climatic conditions, thereby increasing local production and reducing dependency on imports. Despite the growing interest in Camelina’s commercialization, there remains a notable lack of awareness and research regarding its potential applications and benefits within the Ethiopian context. The successful integration of Camelina into Ethiopia’s agricultural framework could significantly alleviate the current oil shortage while contributing to sustainable agricultural practices and rural development. Future research should prioritize the development of high-yielding varieties suited to Ethiopia’s agro-ecologies and cost-effective, locally adapted post-harvest processing techniques to enhance value addition and market competitiveness. Increased investment in research and development, along with targeted policy support, will be essential to fully realizing the crop’s potential in enhancing the country’s oilseed production and ensuring a sustainable food supply.